An updated earthquake catalog for Bangladesh: an attempt at a seismic risk evaluation - Salman, Md Abdullah; Nomaan, Md Saleh Shakeel; Saha, Ayon (Geology, Geophysics and Environment, 2023)
A unique, consistent, and uniform earthquake catalog is crucial for assessing seismic hazards in any locality. This study aims at compiling and processing a better uniform earthquake catalog, using this catalog to identify the probable subduction zone, and assessing seismicity parameters for Bangladesh. The study area is bounded by the geographical limits 16–29°N and 86–96°E. It includes a sum of 48,342 events which are compiled as 1.0 to 8.5 magnitudes (MW) and time period from 1548 to 2020 yrs. Uniformization is made between the body, surface wave, and moment magnitude scales to unify the catalog in terms of MW. For seismic hazard assessment or prediction studies, this catalog comprises earthquake events from Bangladesh and adjoining regions. The assessed MC obtained is around 4.0–5.0, which leads to a, b value varying between 0.71–1.12 and an a value varying between 4.85–7.12. The findings show that the MC is lower at the border of the Chittagong-Sylhet through Hill tracts than the northern part of the area with an MC 4.5–5.0 and a, b value close to 1.00. The results indicate that the study area is a seismically highly active zone in the context of seismicity parameters. Finally, the compiled catalog, seismicity of the area and a probable deformation front are presented and are recommended for use in assessing seismic hazard analysis in Bangladesh.